Management of collar rot of cowpea caused by rhizoctonia solani kuhn using biofumigants - Aparna K P (Department of Plant Pathology, College of Agriculture, 2017)
The study entitles “Management of collar rot of cowpea caused by Rhizoctonia solani kuhn using biofumigants” was undertaken in the Department of Plant Pathology, College of Agriculture, Vellayani during 2015-2017 with the objective to evaluate biofumigant nature of plants, plant oils and oil cakes against Rhizoctonia solani and to develop an ecofriendly management strategy for collar rot of cowpea using biofumigation.